2020
DOI: 10.3390/ma13183982
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Test Setups for the Experimental Evaluation of the Primary Fixation Stability of Acetabular Cups

Abstract: Sufficient primary fixation stability is the basis for the osseointegration of cementless acetabular cups. Several test methods have been established for determining the tilting moment of acetabular press-fit cups, which is a measure for their primary fixation stability. The central aim of this experimental study was to show the differences between the commonly used lever-out test method (Method 1) and the edge-load test method (Method 2) in which the cup insert is axially loaded (1 kN) during the tilting proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The push-on forces applied to reach a predefined position increased with increasing density of the artificial bone material, as it is observed for acetabular cups. 22,28,29 Moreover, the push-on forces increased with enhanced diametrical press-fit. The highest push-on force observed was in a similar range to the assembly forces that are used in standard THA when the ball head is assembled to the stem taper.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The push-on forces applied to reach a predefined position increased with increasing density of the artificial bone material, as it is observed for acetabular cups. 22,28,29 Moreover, the push-on forces increased with enhanced diametrical press-fit. The highest push-on force observed was in a similar range to the assembly forces that are used in standard THA when the ball head is assembled to the stem taper.…”
Section: Discussionmentioning
confidence: 96%
“…In previous in vivo and experimental studies, the frictional moments of various bearing materials and sizes were determined. 19,20,3335 Riva et al analyzed frictional moments of CoC bearings with a diameter of 57 mm with loading according to ISO 14242-3, which ranged from 6.5 to 6.9 Nm. 20 Therefore, the frictional moments determined by Riva et al 20 already reached up to 81% of the turn-off moments determined in the present study, where the smaller-sized HRA was inserted in a low-density foam with the smaller press-fit.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Insufficiently forceful hammering may result in inadequate initial fixation, leading to early cup loosening, while excessive hammering may cause intraoperative acetabular fracture. Several mechanical tests are available to confirm the cup stability intraoperatively, including the torque test, 4,7 lever-out test, [8][9][10] and hands-free test. Although these tests are useful, they are invasive and potentially destructive to surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In the Special Issue, seven papers were published which explore different contexts in which the design of novel loading systems constituted the originality of the research. They range from the characterization of the mechanical behavior of biomaterials [ 1 , 2 ] and of biological tissues [ 3 ], to the verification of the structural behavior of more or less complex medical devices [ 4 , 5 ], from the design of tests for verifying the stability of articular prosthetic components once coupled to the bone [ 6 ], to the simulation of the erosive effect of surgical meshes on the biological soft tissues with which they interface [ 7 ].…”
mentioning
confidence: 99%
“…Several test methods have been established for determining the tilting moment of acetabular press-fit cups, which is a measure for their primary fixation stability. The central aim of the experimental study explained in [ 6 ] is to show the differences between the commonly used lever-out test method and the edge-load test method in which the cup insert is axially loaded during the tilting process with respect to the parameters, tilting moment, and interface stiffness. At last, the research shown in [ 7 ] deals with the phenomenon of meshes erosion whereby soft tissue becomes damaged as a result of contact with implants made from surgical mesh, a fabric-like material consisting of fibers of polypropylene or other polymers.…”
mentioning
confidence: 99%